Firma de convenio. (UNED, 2024)
Aparece Rosario Arias Quirós, primera de izquierda a derecha, le sigue Vigny Alvarado Castillo, al centro de la mesa Rodrigo Arias Camacho y a la par José María Figueres Olsen